Platelet inhibition with standard vs. lower maintenance dose of ticagrelor early after myocardial infarction (ELECTRA): a randomized, open-label, active-controlled pharmacodynamic and pharmacokinetic study. Issue 3 (23rd January 2019) - Kubica, Jacek; Adamski, Piotr; Buszko, Katarzyna; Barańska, Malwina; Sikora, Joanna; Marszałł, Michał Piotr; Sobczak, Przemysław; Sikora, Adam; Kuliczkowski, Wiktor; Fabiszak, Tomasz; Kubica, Aldona; Jilma, Bernd; et al.
Abstract: Aims: Currently available data indicate that reduction of ticagrelor maintenance dose (MD) 1–3 years after acute myocardial infarction (AMI) not only provides sufficient platelet inhibition but also can improve ticagrelor's safety profile. The aim of this study was to compare the antiplatelet effect of reduced and standard ticagrelor MD in stable patients beginning 1 month after AMI. Methods and results: In a single-centre, randomized, open-label, active-controlled trial, on Day 30 following AMI, 52 patients (26 in each study arm) were assigned in a 1:1 ratio to receive either reduced (60 mg b.i.d) or standard (90 mg b.i.d) ticagrelor MD for the following 2 weeks. On Day 45 after AMI the antiplatelet effect of ticagrelor was evaluated with the VASP assay and Multiplate, and there were no significant differences in platelet inhibition between patients on reduced vs. standard MD [VASP: 10.4 (5.6–22.2) vs. 14.1 (9.4–22.1) platelet reactivity index; P = 0.30; Multiplate: 30.0 (24.0–39.0) vs. 26.5 (22.0–35.0) U; P = 0.26]. Likewise, no differences were found regarding the prevalence of on-ticagrelor high platelet reactivity between patients on ticagrelor 60 mg b.i.d vs. 90 mg b.i.d (VASP: 4% vs. 8%; P = 0.67; Multiplate: 15% vs. 8%; P = 0.54). Administration of reduced MD resulted in proportionally lower plasma concentrations of ticagrelor and its active metabolite on Day 45 after AMI. Conclusion: These results suggest that lowering ticagrelor MD 1 month after AMI confers an adequate antiplatelet effect that is comparable to the standard dose. The tested strategy warrants further research to assess its clinical efficacy and safety. ClinicalTrials.gov Identifier: NCT03251859.